Contraceptives Supply Chain and Management in Dayak Societies: A Case Study in Indonesia - Lamia Diang Mahalia; Lutfi Agus Salim; Tika Indiraswari; Iswari Hariastuti (Indian Journal of Forensic Medicine & Toxicology, 2021)
Contraceptive devices and medicine have a very strategic value in supporting family planning operations.This study therefore aims to determine the trend of contraceptive need and usein Dayak societies, andanalyze the supply chain as well as the management of contraceptives required to fullfill this need. Theresearch design used a case study, and qualitative data were obtained from in-depth interviews supported bysecondary data. Meanwhile, quantitative data were collected through questionnaire survey, and data analysiswas performed using the triangulation method. Subsequently, the results of qualitative data analysis werecombined with the results of quantitative data analysis to acquire final conclusions. In Dayak societies,injections are the contraceptive form most required and used by people in the local community (30.21%).Furthermore, there is a significant correlation between need and use of contraceptives (Sig. = 0.000). Thedemand for contraceptives is based on the remaining stock at the health center, as well as the community’srequest. During the acceptance process, the quality, quantity, and type of contraceptives are checked, andcounseling is provided, especially for new acceptors. Meanwhile, the suitability of the contraceptive storageconditions at the health center was discovered to be 61.46%, compared to the standard. Currently, supportingmanagement isnot run optimally, especially in terms of formulatingan operating standard procedure, aswell as monitoring, evaluating, and implementing training.Thus, the availability of contraceptives at thesupplier and local community’s need for contraceptives are taken into consideration and as a strategy formanaging contraceptives in the Primary Health Care of Dayak societies, in order to ensure the availabilityof contraceptives at Puskesmas and fullfill the contraceptive needs of Dayak societies.